Pseudocapillaria (Ichthyocapillaria) bumpi n. sp. (Nematoda: Capillariidae) Parasitising West African Lungfish Protopterus annectens (Owen, 1839) (Lepidosireniformes: Protopteridae) in Mozambique and Its Phylogenetic Position Within Capillariid Nematodes - (:unkn) unknown (My University, 2021)
IntroductionPseudocapillaria (Ichthyocapillaria) bumpi n. sp. (Nematoda: Capillariidae) is described from specimens infecting the digestive tract of the West African lungfish, Protopterus annectens (Owen) (Lepidosireniformes: Protopteridae).MethodsNematodes were collected in Karingani Game Reserve, Southern Mozambique and studied using light microscopy; obtained sequences of the 18S ribosomal (18S rRNA) gene used for phylogenetic studies.ResultsThe new species is assigned to Pseudocapillaria Freitas, 1959 by having a stichosome consisting of a single row of stichocytes and ventrolateral lobes on the male tail as well as by lacking spines on the specular sheath, caudal alae, a membranous caudal bursa, and a lateral expansion of the caudal end. It is also assigned to the sub-genus Ichthyocapillaria Moravec, 1982 by having a membrane between the ventrolateral lobes and by lacking a vulvar appendage. Pseudocapillaria (I.) bumpi n. sp. differs from its nominal congeners by having a comparatively large body size with relatively long spicule, bearing the thin membrane non-extending further than ventrolateral lobes in males and relatively smaller eggs without protruding polar plugs. It is the 20th species of the genus, the first from the Afrotropical Realm, and the first from any lungfish species. Phylogenetic analyses suggested that P. (I.) bumpi is deeply nested in a clade that associates species of the genera Pearsonema, Aonchotheca and Baruscapillaria.
Keywords: African Research